The image of a woman of colour and native American woman in two Kerouac novels - Rožman Ivančič, Nejc (ELOPE (Ljubljana), 2019)
The article examines the portrayal of a woman of colour in the novel The Subterraneans (1958), and the portrayal of a Native American woman in the novel Tristessa (1960). The two works are representative examples within the opus of the American writer Jack Kerouac (1922-1969), and offer suitable starting points for the reinterpretation of his attitude towards women and non-white ethnicities. The novels reveal the ethnocentric, even colonizing attitude of the dominating male narrator in relation to the dominated and subjugated social groups. Although the treated works are considered Kerouac's "female-centred novels" (Phelan Lyke 1991, v), this syntagm is problematized here by showing that the male narrator remains the true protagonist, focused essentially on his own perceptions of the non-white romantic subject, whereas the two female characters are (mere) objects for the protagonists' self-discovery, life experience and psychological projection. In this sense, Kerouac's consistent presentation of women as representatives of an identity of the exotic/Other reveals his nested gender and racial prejudice.
Keywords: ameriška književnost; ameriška proza; drugost; Kerouac, Jack; Kerouac, Jack: The Subterraneans; Kerouac, Jack: Tristessa; kolonialistični diskurz; literarne študije; rasni predsodki; romani; spolni predsodki; ženski liki